Molecular Cloning, Expression Analysis and Localization of Exo70A1 Related to Self Incompatibility in Non-Heading Chinese Cabbage (Brassica campestris ssp. chinensis) - Li WANG; Ting-ting GE; Hai-tao PENG; Cheng WANG; Tong-kun LIU; Xi-lin HOU; Ying LI (Journal of Integrative Agriculture, 2013)
The exocyst is a conserved protein complex, and required for vesicles tethering, fusion and polarized exocytosis. Exo70A1, the exocyst subunit, is essential for assembly of the exocyst complex. To better understand potential roles of Exo70A1 in non-heading Chinese cabbage (Brassica campestris ssp. chinensis), we obtained the full-length cDNA of Exo70A1 gene, which consisted of 1917 bp and encoded a protein of 638 amino acids. BlastX showed BcExo70A1 shared 94.9% identity with Brassica oleracea var. acephala (AEI26267.1), and clustered into a same group with other homologues in B. oleracea var. acephala and Brassica napus. Subcellular localization analysis showed BcExo70A1 was localized to punctate structures in cytosol of onion epithelial cells. Results showed that BcExo70A1 was widely presented in stamens, young stems, petals, unpollinated pistils, roots and leaves of self compatible and incompatible plants. The transcripts of BcExo70A1 in non-heading Chinese cabbage declined during initial 1.5 h after incompatible pollination, while an opposite trend was presented after compatible pollination. Our study reveals that BcExo70A1 could play essential roles in plant growth and development, and is related to the rejection of self pollen in non-heading Chinese cabbage.